2021
DOI: 10.1002/sus2.37
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism understanding for stripping electrochemistry of Li metal anode

Abstract: The pursuit of sustainable energy has a great request for advanced energy storage devices. Lithium metal batteries are regarded as a potential electrochemical storage system because of the extremely high capacity and the most negative electrochemical potential of lithium metal anode. Dead lithium formed in the stripping process significantly contributes to the low efficiency and short lifespan of rechargeable lithium metal batteries. This review displays a critical review on the current research status about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 299 publications
(267 reference statements)
0
62
0
Order By: Relevance
“…[1][2][3][4] It is reported that employing active metals (such as Li, Na, Zn and K) as anodes directly is a hopeful method to significantly enhance the energy density of batteries. [5][6][7][8][9][10][11][12][13][14] Among them, the sodium metal anode (SMA) has attracted great interest benefiting from its high theoretical capacity (1166 mA h g À1 ), low redox potential (À2.71 V vs. standard hydrogen electrode) and cost-effectiveness. [15][16][17][18][19][20] However, the practical application of SMAs is crucially hampered by dendrite growth and ''dead'' Na generation, which are principally derived from the uncontrolled Na deposition, leading to poor Coulombic efficiency, short cycle lifespan and even safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It is reported that employing active metals (such as Li, Na, Zn and K) as anodes directly is a hopeful method to significantly enhance the energy density of batteries. [5][6][7][8][9][10][11][12][13][14] Among them, the sodium metal anode (SMA) has attracted great interest benefiting from its high theoretical capacity (1166 mA h g À1 ), low redox potential (À2.71 V vs. standard hydrogen electrode) and cost-effectiveness. [15][16][17][18][19][20] However, the practical application of SMAs is crucially hampered by dendrite growth and ''dead'' Na generation, which are principally derived from the uncontrolled Na deposition, leading to poor Coulombic efficiency, short cycle lifespan and even safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…As the discharge process went on, the Zn anode continued to dissolve and the light gray shell crumpled (inset of Figure 2b III), similar to the crumpled SEI on the surface of a lithium dendrite after stripping of lithium. [16][17][18][19][20] Electron diffraction pattern (EDP) and energy dispersive X-ray spectroscopy (EDS) mapping characterization of the Zn anode after discharge were performed to investigate the phase structure and chemical elements distribution. The EDP from the initial Zn anode shows sharp diffraction spots indexed as the single crystal Zn (Figure 2d, I).…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] It is a consensus that the construction of the SEI with uniform structure and composition is favorable for the homogeneous stripping/plating of Li metal anode. [ 17 ] Therefore, prefabricating an artificial solid–electrolyte interface (SEI) (e.g., in situ LiF, [ 18 ] lithium‐antimony [Li 3 Sb] alloy/lithium fluoride [LiF], [ 19 ] CNF‐g‐PSSLi, [ 20 ] Li 2 S, [ 21 ] , etc.) on the surface of lithium metal anodes is considered to be a valuable approach.…”
Section: Introductionmentioning
confidence: 99%